Reproductive behavior of the captive Sunda pangolin (Manis javanica Desmarest, 1822). Issue 2 (18th November 2019) - Zhang, Fuhua; Yu, Yishuang; Yu, Jiaming; Wu, Shibao; Li, Shaoshan; Wang, Qiaoyun; Min, Yue; Sun, Ruyong
Abstract: Understanding reproductive behavior is important for the conservation of endangered species, but research on the reproductive behavior of Sunda pangolins ( Manis javanica Desmarest, 1822) is still very scarce. In this study, we used focal animal sampling and all‐occurrence recording by an infrared monitor to observe the behaviors of two Sunda pangolins during a 5‐day breeding period at the Pangolin Research Base for Artificial Rescue and Conservation Breeding of South China Normal University (PRB‐SCNU). The behavioral characteristics and breeding strategies were analyzed, and the results were discussed together with information on other captive Sunda pangolin pairs at PRB‐SCNU. The results found that there was no obvious estrus behavior in the captive female, while the male could exhibit sexual excitement and courtship behavior after a brief introduction period. Repeated copulation continued over many days after the female accepted the courtship. The average duration of copulatory behavior was 248.9 ± 148.7 s ( n  = 25), and all copulation occurred between 20:00 and 08:00 hr in the natural day–night photoperiod. The mating position of Sunda pangolins was lateral–ventral and was classified as the ninth or eleventh pattern under both Dewsbury's and Dixson's classification systems. This study can provide scientific guidance for the captive breeding and management of Sunda pangolins and other pangolin species, which is of great significance for ex situ conservation tactics. Abstract : Research Highlights: In this study, there was no obvious estrus behavior in the captive female Sunda pangolin. The female had repeated mating behaviors during an estrus. And the Sunda pangolin mates in the lateral–ventral posture.